Dyadic coping and well-being in early-stage dementia couples - Muijres, Peter; Bodenmann, Guy; Nussbeck, Fridtjof W.; Jenewein, Josef (Frontiers in Psychiatry, 2025)
IntroductionThis study examined the relationship between dyadic coping (DC) and anxiety, depression, and quality of life in 37 couples facing early-stage dementia (ESD).MethodsThe Actor-Partner Interdependence Model was used for the analyses.ResultsThe study revealed significant actor effects of DC on these outcomes, particularly for quality of life domains. Subjects with ESD providing more delegated DC and engaging more in common DC showed less anxiety. Caregiving partners experienced lower distress when engaging in emotion-focused common DC. Interestingly, positive DC from caregiving partners was associated with lower quality of life in patients.DiscussionWe found more actor effects than partner effects, suggesting that DC behaviors primarily impact one’s own well-being, rather than the partner’s well-being. The different patterns of DC effects on subjects with ESD and their partners reflect a need for tailored interventions that consider the unique needs of each partner in couples facing ESD.